Baseline Arterial CO2 Pressure Regulates Acute Intermittent Hypoxia-Induced Phrenic Long-Term Facilitation in Rats - Perim, Raphael R.; El-Chami, Mohamed; Gonzalez-Rothi, Elisa J.; Mitchell, Gordon S. (Frontiers in Physiology, 2021)
Moderate acute intermittent hypoxia (mAIH) elicits a progressive increase in phrenic motor output lasting hours post-mAIH, a form of respiratory motor plasticity known as phrenic long-term facilitation (pLTF). mAIH-induced pLTF is initiated by activation of spinally-projecting raphe serotonergic neurons during hypoxia and subsequent serotonin release near phrenic motor neurons. Since raphe serotonergic neurons are also sensitive to pH and CO2, the prevailing arterial CO2 pressure (PaCO2) may modulate their activity (and serotonin release) during hypoxic episodes. Thus, we hypothesized that changes in background PaCO2 directly influence the magnitude of mAIH-induced pLTF. mAIH-induced pLTF was evaluated in anesthetized, vagotomized, paralyzed and ventilated rats, with end-tidal CO2 (i.e. a PaCO2 surrogate) maintained at: 1)  39 mmHg (hypocapnia); 2) 41 mmHg (normocapnia); or 3)  48 mmHg (hypercapnia) throughout experimental protocols. Although baseline phrenic nerve activity tended to be lower in hypocapnia, short-term hypoxic phrenic response, i.e. burst amplitude (Δ = 5.1±1.1 µV) and frequency responses (Δ = 21±4bpm), was greater than in normocapnic (Δ = 3.6±0.6 µV and 8±4, respectively) or hypercapnic rats (Δ = 2.0±0.6 µV and -2±2, respectively), followed by a progressive increase in phrenic burst amplitude (i.e. pLTF) for at least 60 minutes post mAIH. pLTF in the hypocapnic group (Δ = 4.9±0.6 µV) was significantly greater than in normocapnic (Δ = 2.8±0.7 µV) or hypercapnic rats (Δ = 1.7±0.4 µV). In contrast, although hypercapnic rats also exhibited significant pLTF, it was attenuated versus hypocapnic rats. When pLTF was expressed as percent change from maximal chemoreflex stimulation, all pairwise comparisons were found to be statistically significant (p < 0.05). We conclude that elevated PaCO2 undermines mAIH-induced pLTF in anesthetized rats. These findings contrast with well-documented effects of PaCO2 on ventilatory LTF in awake humans.